Geometric Manipulation of a Decoherence-Free Subspace in Atomic Ensembles - Chen, Dongni; Luo, Si; Ying-Dan, Wang; Chesi, Stefano; Mahn-Soo Choi (arXiv.org, 2021)
We consider an ensemble of atoms with \(Λ\)-type level structure trapped in a single-mode cavity, and propose a geometric scheme of coherent manipulation of quantum states on the subspace of zero-energy states within the quantum Zeno subspace of the system. We find that the particular subspace inherits the decoherence-free nature of the quantum Zeno subspace and features a symmetry-protected degeneracy, fulfilling all the conditions for a universal scheme of arbitrary unitary operations on it.